Antibacterial activity and chemical analysis of methanolic extracts of Piper sarmentosum Roxb - Syed Ab Rahman, Sharifah Farhana (2015)
Piper sarmentosum Roxb. is a cultivated plant that is also found wild in South East Asia. It is well known due to its medicinal properties and a variety of active chemical constituents. The potential of the plant extract against bacterial leaf blight and sheath brown rot of rice caused by Xanthomonas oryzae pv. oryzae and Pseudomonas fuscovaginae, respectively, were evaluated in this study. The leaf and fruit of P. sarmentosum were extracted using aqueous methanol 80% (v/v) and the yield percentage of crude extracts obtained was 7.5% and 7.1% for the fruit and leaf extract, respectively. The antibacterial activities of the methanolic leaf extract of P. sarmentosum were screened for potential use as a biological control agent against rice pathogenic bacteria by agar well diffusion assay. The concentrations of the extract tested were 25, 50, 100 and 200 mg/mL. The zone of inhibition produced by the extract against the strains was measured and compared with standard antibiotic streptomycin sulfate (30 μg/mL). The leaf extract showed antibacterial activity against X. oryzae pv. oryzae and P. fuscovaginae with the diameter of the inhibition zone ranging from 9.00±0.00 to 19.33±1.53 mm. Similarly, the fruit extract also showed positive inhibition against the tested bacteria with the diameter ranging from 9.33±0.58 to 19.33±1.15 mm. Positive control, streptomycin sulfate, showed inhibition against all the tested bacterial isolates with the range of 17.67±0.58 to 18.00±1.73 mm for the leaf extract and 15.67±5.13 to 21.00±3.46 mm for the fruit extract. Negative control, aqueous methanol 80% (v/v), showed no inhibition zone against any microorganism for both the leaf and fruit extracts. The Minimal Inhibition Concentration (MIC) and Minimal Bactericidal Concentration (MBC) were then determined. The MIC was obtained at 12.5 mg/mL for both tested bacteria while for MBC; it was at 12.5 mg/mL for X. oryzea and 25.0 mg/mL for P. fuscovaginae. For the fruit extract, the MBC value obtained for both P. fuscovaginae and X. oryzae were at 25.0 mg/mL. The phenolic compounds present in the leaf and fruit extracts of P. sarmentosum were further identified using HPLC analysis. Five standards were used in the analysis – caffeic acid, tannic acid, gallic acid, quercetin and naringin. The identification of each compound was based on a combination of retention time and spectral matching. The phenolic compounds were separated and quantified in the analysis to obtain the amount of the phenolic compounds present in each of the samples. The fraction of the elute containing the purified compound was collected and further tested for antibacterial activity against the pathogenic bacteria. All of the collected fractions, which were detected as the phenolic compounds based on the standard used, showed positive inhibition against the tested bacteria. The results obtained from this study suggest that the leaf and fruit extracts of P. sarmentosum have potential to be developed as a novel bactericide.